Gas transport through cork: Modelling gas permeation based on the morphology of a natural polymer material - Brazinha, Carla; Fonseca, Ana P.; Pereira, Helena; Teodoro, Orlando M. N. D.; Crespo, João G. (Journal of Membrane Science, 2013)
Natural polymers have been studied during the last years for the transport and separation of liquid and gas mixtures, in terms of solubility and permeability data, and their structure and mechanical properties have been characterised. However, no transport models have been reported, relating transport with the material morphology. Cork is a natural cellular material containing three structural polymers (suberin, lignin and polysaccharides). Cork is considered a natural polymer, with economic relevance due to its sealing, non-toxic, stable and low-density properties. Cork was characterised in this work in terms of its solubility and permeability data in relation to various gases with different molecular mass: He, O2, N2, CO2 and 1,1,1,2-tetraﬂuoroethane (R134a). A morphological analysis of the structure of the cork sample chosen in this work was also performed using SEM (scanning electron microscopy) and TEM (transmission electron microscope) image analysis, which took into account the variation of each relevant structural parameter. A transport model was developed supported on the morphology of cork characterised in this work. The transport model developed considers that gas permeation occurs through the plasmodesmata, which are channels with approximately 100 nm of diameter that cross the cell walls of the cork cells. It was found that gas transport follows a Knudsen mechanism, as proved by the gas permeability behaviour with increasing gas molecular mass, with a negligible contribution of viscous transport to the total ﬂux.
Keywords: Cork; Gas permeation; Knudsen transport; Natural polymers; solubility; Solution–diffusion model